Pengaruh Keputusan Investasi, Keputusan Pendanaan dan Kebijakan Dividen Terhadap Nilai Perusahaan pada Perusahaan Sub Sektor Kesehatan yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2020-2022 - Fira, Safira Maulidina; Kusumayadi, Iwan (Postgraduate, University of Mataram, 2024)
This study aims to analyze the influence of Investment Decisions, Funding Decisions and Dividend Policies on Company Value in Health Sub-Sector Companies Listed on the Indonesia Stock Exchange for the 2020-2022 Period. This research is an associative quantitative research. Samples using purposive sampling techniques. The sample amounted to 11 companies from 31 health sub-sector companies listed on the Indonesia Stock Exchange for the 2020-2022 period. Multiple linear regression data analysis technique using SPSS 2022 for windows software. The data analysis used is normality test, heteroscedasticity test, autocorrelation test, multicolonicity test, multiple linear regression test, t test, f test and determination coefficient test. The results showed that Investment Decisions had an insignificant negative effect on company value, Funding Decisions had a positive insignificant effect on company value and Dividend Policy had a negative insignificant effect on company value.